Proceedings of the 51st ACM Technical Symposium on Computer Science Education 2020
DOI: 10.1145/3328778.3366851
|View full text |Cite
|
Sign up to set email alerts
|

Comparing TUIs and GUIs for Primary School Programming

Abstract: There is considerable interest in using tangible user interfaces (TUIs) to support teaching children programming, but evidence for the benefits is mixed, and their deployment in school environments presents more challenges than graphical user interfaces (GUIs). This study investigates the effect of GUIs and TUIs on learning outcomes, attitudes toward computing, and reported enjoyment in a computer-programming activity with primary-school students aged 6-7 in Saudi Arabia. Forty-two students engaged in a 45minu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Existing studies examining the benefits of TUIs for learning programming have reported mixed results, with no clear consensus [38,39,41]. Our recent work [2], which this paper builds on, investigated the relationship between interface type (TUI or GUI) and learning gains, attitude toward computing, and enjoyment of computer-programming activities with primary school students in Saudi Arabia [47]. We found that learning gains were significantly higher for students using a GUI programming environment than those using a TUI.…”
Section: Embodied Cognitionmentioning
confidence: 85%
“…Existing studies examining the benefits of TUIs for learning programming have reported mixed results, with no clear consensus [38,39,41]. Our recent work [2], which this paper builds on, investigated the relationship between interface type (TUI or GUI) and learning gains, attitude toward computing, and enjoyment of computer-programming activities with primary school students in Saudi Arabia [47]. We found that learning gains were significantly higher for students using a GUI programming environment than those using a TUI.…”
Section: Embodied Cognitionmentioning
confidence: 85%
“…In this way, the palette is in the middle. Finally, XLBlocks [69] displays the toolbox at the top of the window and Tica [4] does it in the bottom part.…”
Section: Block-commentsmentioning
confidence: 99%
“…[93] -Teach computational thinking. [162] 4 Scratch Teach computational thinking using experiments of fractal geometry.…”
Section: Name Metatool Topicmentioning
confidence: 99%
See 2 more Smart Citations